Outcomes of Lisfranc Injuries Treated with Joint-Preserving Fixation - Scofield, Harrison O (Indian J Orthop, 2020)
BACKGROUND: Open reduction and internal fixation (ORIF) with transarticular screws to stabilize Lisfranc injuries may increase the risk of arthritis or affect outcomes. Joint-preserving fixation using staples, bridge plating, or Lisfranc screws avoids iatrogenic articular damage. This study analyzes functional outcomes and complications in Lisfranc-injury patients who underwent joint-preserving fixation. MATERIALS AND METHODS: We conducted a retrospective review of patients treated for Lisfranc injury at a Level 1 trauma center from July 2008 to October 2015. Patients over 18 years of age, with no concomitant procedures in the lower extremities, were included. Functional outcomes were evaluated through American Orthopaedic Foot and Ankle Society (AOFAS) scores. RESULTS: Fourteen patients met the inclusion criteria. The average followup time was 57 months (range 22-102 months). AOFAS scores averaged 80.4 (standard deviation [SD] 16) at the time of the latest followup, with time to return to regular activities averaging 34 weeks (SD 25 weeks). Five patients had their hardware removed, and two required subsequent fusion during the followup period. The single complication involved a screw backing out, with subsequent removal. CONCLUSIONS: In this case series, joint-preserving fixation for Lisfranc injuries offered similar AOFAS scores as those reported for ORIF with transarticular screws but with a decreased rate of hardware removal and need for midfoot fusion.